X-Ray Debye Temperatures in a Series of Organic Haloamines† - Yathirajan, H.S.; Mohana, K.N.; Madhava, M.S.; Somashekar, R. (Asian Journal of Chemistry, 2010)
Using the observed X-ray reflection intensities for eight organic haloamines, namely, chloramines-T, chloramines-B, bromamine-T, bromamine-B, dichloramine-T, dichloramine-B, dibromamine-T and dibromamine-B, we have determined Debye-Waller factors and hence Debye temperatures. The results have been compared and analysed in terms of molecular composition.